Low-Power Highly Robust Resistance-to-Period Converter - Luis C. Álvarez-Simón; Emmanuel Gómez-Ramírez; María Teresa Sanz-Pascual (Sensors, 2018)
This paper presents a novel structure of Resistance- to-Period (R-T) Converter highly robust to supply and temperature variations. Robustness is achieved by using the ratiometric approach so that complex circuits or high accuracy voltage references are not necessary. To prove the proposed architecture of R-T converter, a prototype was implemented in a 0.18 <semantics> μ </semantics> m CMOS process with a single supply voltage of 1.8 V and without any stable reference voltage. Experimental results show a maximum ±1.5% output signal variation for ±10% supply voltage variation and in a 3⁻95 <semantics> ° </semantics> C temperature range.